Rural employment and administration in the Third World : development methods and alternative strategies - Harvey, Charles, M.A. (Farnborough, Eng. : Saxon House, 1979)
This study focus on services to the rural dwellers. The author assessed the effects of policy implications arising from an over-riding concern with economic growth.
Includes index.
Bibliography: p. 97-105.
asm; 04/03/19
Loans
Keywords: Rural development